TRAINING OF HIGHLY EDUCATED MEDICAL PERSONNEL IN THE FERGANA VALLEY (IN THE 50-80 YEARS OF THE XX CENTURY) - Najmiddinov, Qodirjon (Educational Research in Universal Sciences, 2023)
This article covers the issues of providing the population with medical staff, their qualifications, the state of modern medical equipment and equipment, vaccination of the population against diseases during the Soviet government period in the Fergana Valley.